Systematic review of dog bite prevention strategies. Issue 3 (7th April 2022) - Duncan-Sutherland, Natasha; Lissaman, Abbey C; Shepherd, Michael; Kool, Bridget
Abstract : Background: The prevention of dog bites is an increasingly important public health topic, as the incidence of serious injury continues to rise. Objectives: To evaluate the effectiveness of interventions to prevent dog bites and aggression. Methods: Online databases were searched (PubMed, Cochrane Library, Embase and Google Scholar), using the search terms: dog/s, canine, canis, kuri, bite/s, bitten, aggression, attack, death, fatal, mortality, injury/ies, prevention, intervention, for studies between 1960 and 2021. All study designs were considered. Outcomes of interest were the incidence of dog bites or dog aggression. Non-English studies, and those without full-text access were excluded. Results: Forty-three studies met the review criteria, including 15 observational and 27 interventional studies. Fifteen studies investigating dog-control legislation, including leash laws, stray dog control and infringements indicated this can reduce dog bite rates. Breed-specific legislation had less of an effect. Six studies investigating sterilisation, showed while this may reduce dog bites through a reduction in the dog population, the effect on dog aggression was unclear. An alcohol reduction programme showed a significant reduction in dog bite rates in one study. Seven studies assessing educational approaches found that intensive adult-directed education may be effective, with one study showing child-directed education was not effective. Eight studies on dog training (two police-dog related), and six evaluating dog medication or diet were generally low quality and inconclusive. Conclusions: Multiple strategies including effective engagement with indigenous communities and organisations will be required to reduce dog-bites and other incidents involving dog aggression. This review provides some evidence that legislated dog control strategies reduce dog bite rates. Available evidence suggests greater restrictions should be made for all dogs, rather than based on breed alone. Due to a burden of child injury, protection of children should be a focus of legislation and further investigations. Prevention strategies in children require redirection away from a focus on child-directed education and future research should investigate the effectiveness of engineering barriers and reporting strategies.